Political Strategy of Adnan Purichta Ichsan Yasin Limpo in the 2015 Election of Regent and Deputy Regent of Gowa Regency - Mausili, Dwi Rianisa; Arsat, Muhamad; Yulandari, Ririn; Nuraliah, Dewi; Nasiruddin, Nurfadilah; Razak, Fitriani Sari Handayani (Journal of Social and Policy Issues, 2025)
Various strategies were carried out by Adnan Purichta Ichsan Yasin Limpo as a young politician who participated in the contest for the election of the regent and deputy regent in Gowa Regency using an independent path, always criticized with various issues, namely primordialism, having a tough opponent, namely the King of Gowa and as a young man who was considered inexperienced. These issues sparked debate, discussion, and public attention at the stages of the regent election in Gowa Regency in 2015. This study uses a qualitative method with a case study design. The data collection method uses in-depth interviews with informants who have adequate capacity and capability. The research instrument uses interview guidelines, and uses a recording application from a mobile phone. Data analysis techniques by means of data collection, data transcription, data selection, data analysis, triangulation, and drawing conclusions. The results of the study show that Adnan Purichta Ichsan Yasin Limpo was successfully elected as Regent for the 2016-2021 period as a portrait of the success of young people. However, the predicate of primordialism could be lost after Adnan Purichta Ichsan Yasin Limpo conducted a Judicial Review to the Constitutional Court. In addition, to fight the King of Gowa, Adnan Purichta Ichsan Limpo must choose the right deputy, use youth issues to legitimize his identity, rely on great communicators, package a persuasive campaign, campaign in the form of dhikr and prayer, rely on volunteer loyalty, and disseminate information through online and offline media to boost his popularity and electability.